2022
DOI: 10.1002/pros.24422
|View full text |Cite
|
Sign up to set email alerts
|

New strategy for the identification of prostate cancer: The combination of Proclarix and the prostate health index

Abstract: Objectives: Prostate health index (PHI) and, more recently, Proclarix have been proposed as serum biomarkers for prostate cancer (PCa). In this study, we aimed to evaluate Proclarix and PHI for predicting clinically significant prostate cancer (csPCa).Patients and Methods: Proclarix and PHI were measured using samples of 344 men from two different centers. All patients underwent prostate biopsy, and among those, 188 men with PCa on biopsy had an additional radical prostatectomy (RP). All men had a prostate-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Combining the single biomarkers of PHI and Proclarix by the ANN approach rather than the final scores by logistic regression analysis, as in our previous work [5], we achieved an improvement in specificity (68% vs. 49%, respectively) for csPCa identification.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Combining the single biomarkers of PHI and Proclarix by the ANN approach rather than the final scores by logistic regression analysis, as in our previous work [5], we achieved an improvement in specificity (68% vs. 49%, respectively) for csPCa identification.…”
Section: Discussionsupporting
confidence: 57%
“…We selected the blood-based proteins of PHI and Proclarix tests as several authors showed that they were significantly associated with an increased risk for a positive biopsy and for a GS of ≥7 at RP [5,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 This test, which incorporates serum total PSA (tPSA), free PSA (fPSA), cathepsin D (CTSD), thrombospondin 1 (THBS1) and patient age, 14 has been shown to detect csPCa with more favourable diagnostic performance characteristics as compared to percent fPSA (%fPSA) and the ERSPC risk calculator. [15][16][17][18][19][20][21][22] One limitation of the available literature on the Proclarix test is that all papers relied upon the results of a 10-14 core systematic biopsy of the prostate with or without targeted biopsy core. 15,[18][19][20] Although this practice is typical in the prostate cancer biomarker literature, concerns remain regarding the accuracy of this somewhat limited method of sampling the prostate.…”
Section: Introductionmentioning
confidence: 99%